The key characteristics and main differences of Space policy of Russian Federation and the USA as the great powers - Vasilev, Aleksei (2020)
The bachelor thesis’s objective is to examine and compare the key characteristics of the United States and the Russian Federation as the great powers with huge capabilities and potential to explore outer space. By making this comparison, the bachelor thesis answers several crucial questions in understanding space policymaking in both countries. The first question is the major differences and common things between the USA and the Russian Federation, as the great powers, in decision-making processes on space policy. The second question stands for how the countries’ private companies contribute to and develop the great powers’ space policy. The last one is the national security question and how the Ministry of Defense of both states cooperate with state-owned corporations in terms of outer space research.